A cyclodextrin-phenylboronic acid cross-linked hydrogel with drug hosting, self-healing and pH-sensitive properties for sustained drug release. (28th May 2021) - Chen, Daijun; Ren, Guanglei; Zhao, Xiaoli; Luo, Jinni; Wang, Huanxia; Jia, Pengxiang
Abstract : This work reports a multifunctional hydrogel using cyclodextrin-phenylboronic acid as a reversible, pH-sensitive cross-linker. Abstract : The rapid drug release and poor self-healing properties of drug-loaded hydrogels largely limit their practical application. Herein, we present a simple method to prepare hydrogels with self-healing, drug hosting and pH-sensitive properties for sustained drug release. First, salicylic acid was loaded into β-CD through host–guest interactions. The hydrogel was then constructed through the polymerization of acrylamide using cyclodextrin-phenylboronic acid as a reversible, pH-sensitive cross-linker. The obtained hydrogel exhibited outstanding stretchability (1150%), good tensile strength (42 kPa), excellent self-healing properties (90%) and high biocompatibility. Besides, the introduction of the cyclodextrin-phenylboronic acid cross-linker endowed the hydrogel with pH-sensitive and sustained drug release properties. These functions enable cyclodextrin-phenylboronic acid cross-linked hydrogels to be drug hosting, self-healing and pH-sensitive flexible materials for sustained drug release, making them a powerful platform for various biomedical applications.